2023
DOI: 10.1128/mbio.01137-23
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar Typhi uses two type 3 secretion systems to replicate in human macrophages and colonize humanized mice

Abstract: Salmonella enterica serovar Typhi ( S . Typhi) is a human-restricted pathogen that replicates in macrophages. In this study, we investigated the roles of the S . Typhi type 3 secretion systems (T3SSs) encoded on Salmonella pathogenicity islands (SPI)-1 (T3SS-1) and SPI-2 (T3SS-2) during human macrophage infection. We found that mutants of S . Typhi deficient for both T3SSs were defective for intramacroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Briefly, pFCcGi contains a constitutively expressed mCherry and an L-arabinose inducible gfp . Prior to infection, S. Typhi pFCcGi is grown in the presence of L-arabinose whereas during infection L-arabinose is removed so that GFP is ‘diluted’ as bacteria replicate 14 , 15 . This plasmid also indicates the viability of intracellular S .…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, pFCcGi contains a constitutively expressed mCherry and an L-arabinose inducible gfp . Prior to infection, S. Typhi pFCcGi is grown in the presence of L-arabinose whereas during infection L-arabinose is removed so that GFP is ‘diluted’ as bacteria replicate 14 , 15 . This plasmid also indicates the viability of intracellular S .…”
Section: Resultsmentioning
confidence: 99%
“…Typhi are not consistent. Some have shown that it is required for replication in human epithelial cells [13] and in human-derived macrophages [14–16]. However, other work has led to the conclusion that it does not contribute to replication in such macrophages [13, 17, 18].…”
Section: Full-textmentioning
confidence: 99%
“…[ 16 ] used the same strains and found that in two separate comparisons, the SPI-2 injectisome accounted for a difference in intracellular growth of at least fourfold over 48 h. More recently, Hamblin et al . [ 15 ] measured the replication of SPI-2 null mutants in primary human and a human-derived THP-1 macrophage cell line. While no differences were detected by c.f.u., a more sensitive method based on replication-associated dilution of a fluorescent protein revealed a replication defect of SPI-2 mutant between 12 and 24 h.…”
Section: Full-textmentioning
confidence: 99%
See 2 more Smart Citations